Epistemologi Hadis Sunni-Syiah: Analisa Terhadap Implikasinya - Siti Fahimah (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2018)
Political upheaval in the early companions resulted in the birth of two major schools of Islam: Shiism and Sunni. In the course of history these two great schools not only have an impact on the split of Muslims but also have an impact on their understanding of the hadith which is the second source after the Qur'an by Muslims, the difference of the interpretive view of the hadith for the Sunni Shia is at the origin of the source is the friend. There are many different views on the meaning and validity of the hadith between Sunni Shiites, it is because their doctrine and adulation is different, one of which is Shia prefers the tradition of written transmissions to oral, other to the Sunni who consider oral and written to be the same if they can accountable kulaitasnya, then in taking the hujjah, Shia did not take the source of the hadith narrated Umar and Uthman, but prioritize Ali. These are the things that are very visible in the different understandings of hadith according to Shia-Sunni.